PENGARUH PENDEKATAN REALISTIC MATHEMATICS EDUCATION TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Amalia, Lela; Sulistyorini, Yunis (Universitas Insan Budi Utomo, 2022)
This study aims to determine whether there is an effect of the Realistic Mathematics Education (RME) approach on students' mathematical problem solving abilities on the subject of social arithmetic for class VII MTs Al-Ihsan. This study uses an experimental design research method with a posttest only control design. The data collection technique used an essay test with 5 questions, analyzed using Microsoft Excel data analyst. From the data that has been analyzed, it is obtained that the average of the experimental group is 81,750, while the average value of the control group is 76,417. Hypothesis analysis in this study using a t-test with a significant level of 5% (0.05) the results obtained tcount= 4.359 and ttable= 2.013, then tcount > ttable. The results of the analysis prove that there is a significant effect of the application of the Realistic Mathematics Education (RME) approach on the mathematical problem solving abilities of seventh grade students of MTs Al-Ihsan.